Effects of oral targeted treatments in pulmonary arterial hypertension: A systematic review and meta-analysis - Zhu, Hui-ru; Kuang, Hong-yu; Li, Qiang; Ji, Xiao-juan (Frontiers in Cardiovascular Medicine, 2022)
Background: Although pulmonary arterial hypertension (PAH) is a fatal disease, specific drugs have been used to treat PAH. These drugs predominantly target these three pathobiological pathways: endothelin receptor antagonist (ERA), nitric oxide (NO), and prostanoids pathways. In this review, we aimed to analyze the efficacy and safety of oral targeted treatments for PAH. Methods: MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials databases were searched. Randomized controlled trials that compared oral targeted drugs with placebos were selected. We calculated odds ratios (ORs) with 95% confidence intervals (CIs) for variables with dichotomous outcomes, and standardized mean differences with continuous outcomes variables. Additionally, the mean of the differences for the 6-minute walk test (6MWD) were analyzed. Results: In total, 23 studies involving 7121 patients were included in this study. These studies show that orally PAH-specific drugs could decrease the risk of clinical worsening events (CWEs), with an OR of 0.55 (P<0.001). Furthermore, these drugs could improve exercise capacity, showing a 21.74-meter increase in 6 MWD (95%CI: 17.53-25.95 meters) and cause a greater amelioration of functional class (OR=0.60, 95%CI: 0.47-0.76). Additionally, subgroup analysis indicated that, compared with placebo, ERAs and drugs in the NO pathway were mostly effective and safe, which are associated with an improvement in exercise capacity, 6MWD, and worsening events-free survival rate. Conclusions: NO exhibited the most prominent clinical effect on exercise tolerance. However, in the subgroup analysis, oral targeted drugs of different pathways show applicability to different populations, which highlights the need for precise treatment in the clinical setting.